Unique lanthanide frameworks with 63 topology based on 1, 5-naphthalenedisulfonate and 1H-imidazo[4, 5-f][1, 10]-phenanthroline: syntheses, crystal structure, photoluminescence, and white light emission1. Issue 34 (14th September 2015) - Ma, Dou; Huo, Rui; Li, Xia
<x xml:space="preserve">Abstract</x> Lanthanide complexes with a 63 net topology were synthesized. White light emissions were realized by the Sm(iii) complex and Ln(iii)-doped Eu(iii) complexes.